Effectiveness Of Ginger Cumeris Extract With Acupressure On The Intensity Of Menstruation Pain And Low Back Pain In Primary Disminore - Diah Evawanna Anuhgera; Nikmah Jalilah Ritonga (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Pain during primary dysmenorrhea is a normal gynecological condition, but this condition is often detrimental to women who experience dysmenorrhea, including decreased quality of work, absence when experiencing primary dysmenorrhea and disruption of daily activities. One method that is safe and easy to obtain is by administering ginger and turmeric extract accompanied by acupressure to help reduce the intensity of menstrual pain and lower back pain. The purpose of this study was to determine the effectiveness of ginger turmeric extract and acupressure on the intensity of menstrual pain and low back pain in primary dysmenorrhea. This type of quasi-experimental research with a pretest-posttest control group design carried out in the female dormitory of the Lubuk Pakam Medistra Health Institute. The sample in this study were 28 students in the first semester of the Faculty of Nursing who experienced primary dysmenorrhea using a random sample technique. In this study there were two groups, namely the intervention group and the control group. The instruments in this study were the Numeric Rating Scale (NRS) to measure pain during menstruation, the Qswestry Low Back Pain Disability Questionnaire to measure low back pain, and an observation sheet. Data analysis using independent and dependent t-test. The results showed that there were significant differences in the intensity of menstrual pain and low back pain on the first and second days between the intervention group and the control group with p H1 = 0.003 and p H2 = 0.000 (menstrual pain) and p H1&2 = 0.000 (low back pain). . The percentage decrease in the intensity of menstrual pain with intervention was 66.81%, while the percentage decrease in low back pain was 35.29%. Giving turmeric ginger extract and acupressure therapy has been proven effective in reducing the intensity of menstrual pain and low back pain. Health workers can apply and educate this method to women who experience dysmenorrhea and can be used as learning material for pain management in midwifery education courses.